An exploration on customer relationship management and its perspectives: aviation sector - D H, Malini (Journal of Management and Science, 2012)
The CRM approach has received increased attention as a marketing concept during the last decades (Sin et al.2005; Osarenkhoe and Bennani 2007; Wilson et al. 2002). By combining the abilities to respond directly to customer requests and to provide the customer with a highly interactive, customized experience. Organizations today have greater scope for establish, cultivate, and maintain long-term customer relationships than ever before. The ultimate goal is to transform these relationships into greater profitability by increasing repeat purchase rates and reducing customer acquisition costs. Indeed, this revolution in customer relationship management or CRM as it is called has been referred to as the new ―mantra‖ of marketing (Russell S. Winer 2001). The Indian aviation industry is identified as one of the fastest growing industry in the world with private airlines accounting for more than 75 per cent of the sector. It is noticed that the 9th largest position in the aviation market in the world is India. In the present study the effort has been made to examine and analyze the effects of CRM and its contribution towards airline industry and also to develop and clarify a conceptual framework integrating CRM constructs, and its implications on aviation industry.